Students’ Perceptions of Learning English Grammar through Problem-Based Learning - Nurmulyana Js; Baso Jabu; Abdullah (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
The purpose of this study is to investigate how students feel about using problem-based learning (PBL) to learn English grammar. Students frequently view grammar as a challenging and uninteresting part of learning English. As a result, PBL was introduced as a student-centered strategy that promotes involvement, teamwork, and problem-solving grounded in actual situations. First-grade children from SMPN 1 Duapitue Sidrap participated in this study, which used a qualitative research approach. Open-ended questionnaires that let students share their thoughts and experiences with grammar instruction using PBL were used to gather data. To find recurrent themes and patterns in the students' answers, a descriptive analysis of the data was conducted. The results show that when it came to learning English grammar, students usually thought well of problem-based learning. PBL, according to students, improved their motivation to learn grammar, encouraged active participation in class activities, and made it easier for them to understand grammatical principles. Additionally, by promoting collaboration, critical thinking, and conversation, PBL created a more meaningful learning environment. According to these results, problem-based learning is seen to be a useful strategy for improving students' learning experiences and promoting grammar acquisition in EFL classes.